2006
DOI: 10.1111/j.1365-2672.2006.02817.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multi Locus Sequence Typing to the analysis of the biodiversity of indigenous Saccharomyces cerevisiae wine yeasts from Lebanon

Abstract: Aims:  To assess suitability of Multi Locus Sequence Typing (MLST) for investigating the biodiversity of wine yeast strains. This method was compared with established ones like microsatellite analysis or amplification of genomic regions flanked by repeated (delta) elements. Methods and Results:  DNA fragments were amplified and sequenced for 26 loci representing housekeeping genes, open reading frames (ORFs) of unknown functions or intergenic regions. A set of seven loci was tested on 84 Saccharomyces cerevisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 46 publications
4
49
0
1
Order By: Relevance
“…Of the remaining wine strains not included in the ''wine'' cluster, three commercial strains-Primeur, 71B, and S101-reside in a small cluster on the left side, highlighted in orange, that also contains the remaining two bread strains (Morocco Bread and Sardinian Commercial, which are extremely similar to each other based on this analysis); this is in agreement with studies reporting that the Primeur and 71B wine yeasts have genomic similarity to bread yeasts by both microsatellite repeat and multilocus sequence analysis (Fay and Benavides 2005a;Ayoub et al 2006;Legras et al 2007). The remaining nine commercial wine strains do not appear in any distinct clusters.…”
Section: Subtelomeric Regionssupporting
confidence: 79%
See 1 more Smart Citation
“…Of the remaining wine strains not included in the ''wine'' cluster, three commercial strains-Primeur, 71B, and S101-reside in a small cluster on the left side, highlighted in orange, that also contains the remaining two bread strains (Morocco Bread and Sardinian Commercial, which are extremely similar to each other based on this analysis); this is in agreement with studies reporting that the Primeur and 71B wine yeasts have genomic similarity to bread yeasts by both microsatellite repeat and multilocus sequence analysis (Fay and Benavides 2005a;Ayoub et al 2006;Legras et al 2007). The remaining nine commercial wine strains do not appear in any distinct clusters.…”
Section: Subtelomeric Regionssupporting
confidence: 79%
“…Numerous methods have been used to assay genomic variation in yeast and determine relationships between strains, and also used to infer strain origins and history (e.g., Schuller et al 2004;Legras et al 2005). Such studies include comparative analyses of microsatellites (Legras et al 2007;Franco-Duarte et al 2009;Muller and McCusker 2009b;Richards et al 2009), mini-and megasatellites (Richard and Dujon 2006;Rolland et al 2010), copy number variation using aCGH (Pérez-Ortín et al 2002;Infante et al 2003;Winzeler et al 2003;Dunn et al 2005;Carreto et al 2008;Kvitek et al 2008), and polymorphisms detected by tiling arrays (Schacherer et al 2009), as well as the use of multispecies 131-gene taxonomic microarrays (Muller and McCusker 2009a) and Multi Locus Sequence Typing (MLST) (Fay and Benavides 2005a,b;Ayoub et al 2006;Vigentini et al 2009). These studies have mostly shown that yeasts used for a particular industrial use appear to be more closely related, but that geographical migrations, as well as genetic drift, have influenced diversity among S. cerevisiae populations (Legras et al 2007).…”
mentioning
confidence: 99%
“…For example, within the sequenced diploid strain SC5314 of the human pathogenic yeast Candida albicans, there is an SNP frequency of~1 % per nucleotide (Jones et al, 2004). Similarly, a survey of seven genomic loci (3013 nt in total) for 84 natural strains of the model yeast Saccharomyces cerevisiae from Asia has identified a total of 62 SNPs, yielding an SNP frequency of 2.05 % per nucleotide (Ayoub et al, 2006). The SNP frequencies are higher in populations of several opportunistic pathogenic yeasts, such as Candida parapsilosis (~3.4 %; Fundyga et al, 2004), and the species complexes of Candida guilliermondii (~6.3 %; Lan & Xu, 2006) and Cryptococcus neoformans (~20 % per nucleotide; Xu et al, 2000b).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, most researchers who set up MLST systems for other bacteria followed this tradition. However, when MLST systems were used in fungal pathogens, it was observed that the discriminatory power was often not satisfactory when only housekeeping genes were used (1,27,34). On the other hand, when one or two nonhousekeeping genes were also included as targets, the discriminatory power was improved (19,21).…”
Section: Discussionmentioning
confidence: 99%